Efektivitas langkah-langkah peregangan (stretching) untuk menurunkan nyeri dismenore di wilayah Sleman Yogyakarta - Sherkia Ichtiarsi Prakasiwi (Jurnal Kebidanan, 2020)
Dysmenorrhea is an imbalance of the hormone progesterone in the blood, causing pain to arise. Women have experienced 90% of dysmenorrhea, this disturbs 50% of women of reproductive age and 60-85% in adolescence, which results in many absences in schools and offices. Non-pharmacological solutions are seen as safer, one of which is stretching which aims to make muscles and joints flexible and elastic. This is due to increased levels of endorphins, epinephrine, dopamine and serotonin produced by the brain due to exercise. This study aims to determine stretching steps to reduce dysmenorrhea pain in the Sleman region. The method of this research is a different test study with a cross sectional type of research. The research sample was 60 female students. The sampling technique was purposive sampling, bivariate analysis techniques using the Mann Whitney statistical test using SPSS software. The results of the Mann Whitney test in the control group and the intervention group showed a p-value of 0,000 (ɑ <0.05) indicating that there were differences between the control and intervention groups in decreasing the level of pain in dysmenorrhea where the mean pain level of dysmenorrhea was 4 50 while in the intervention group the average is only 0.13 so that it gets ∆ mean of -4.37. This proves that stretching is more influential in decreasing the level of pain in dysmenorrhea than in stretching.